2021
DOI: 10.3390/ijerph18168843
|View full text |Cite
|
Sign up to set email alerts
|

Review: Prevalence of Addictions among Transgender and Gender Diverse Subgroups

Abstract: We conducted an analysis of the prevalence of substance and behavioral addictions across different transgender and gender diverse (TGD) subgroups. We performed a scoping review using MEDLINE and Google Scholar databases and examined 12 addictions, including alcohol, nicotine, cannabis, illicit drugs, gambling, eating/food, internet, sex, love, exercise, work, and shopping. We presented prevalence rates for each addiction as a function of an individual’s gender identity (stratified into transgender females, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 68 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…The current lack of measurement and reporting of sample gender information [85] makes it difficult to know for example whether trans and/or nonbinary individuals were included and whether the authors assessed sex assigned at birth (suggested by the use of "male"/ "female" terminology) or gender identity ("men"/ "women" terminology). More transparent and rigorous reporting of gender and inclusion of more than one gender and sexual orientation group in studies on PPU is especially important when we consider that these person characteristics have been shown to interact with other behavioral addictions as well as substance abuse [86][87][88]. An issue complicating the integration of findings across experiments is the diversity of stimuli.…”
Section: Limitationsmentioning
confidence: 99%
“…The current lack of measurement and reporting of sample gender information [85] makes it difficult to know for example whether trans and/or nonbinary individuals were included and whether the authors assessed sex assigned at birth (suggested by the use of "male"/ "female" terminology) or gender identity ("men"/ "women" terminology). More transparent and rigorous reporting of gender and inclusion of more than one gender and sexual orientation group in studies on PPU is especially important when we consider that these person characteristics have been shown to interact with other behavioral addictions as well as substance abuse [86][87][88]. An issue complicating the integration of findings across experiments is the diversity of stimuli.…”
Section: Limitationsmentioning
confidence: 99%
“…Although gender-affirming health care improves the well-being of transgender (trans) individuals (ie, transgender, nonbinary, those with culturally specific identities, and others), trans patients continue to report frequent discriminatory and unskilled treatment in health care spaces . These experiences are associated with suicidality, substance use, and other negative outcomes . Consequently, trans patients sometimes withhold gender-related information to avoid discrimination .…”
Section: Introductionmentioning
confidence: 99%
“…Transgender women have a disproportionately high HIV prevalence when compared to other high-risk groups (HRGs), including MSM and sexual partners of people living with HIV. This is thought to be linked to high-risk sexual activities such as commercial sex work and unprotected receptive anal intercourse [5].…”
Section: Introductionmentioning
confidence: 99%